Adhesive and separator containing same
Patent Information
- Application Number
- JP2023569613
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-09-27
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2042-09-27
Smart Images

Figure 0007635428000018 
Figure 0007635428000019 
Figure 0007635428000020
Abstract
Description
[Technical field]
[0001] The present application relates to the technical field of lithium batteries, in particular to an adhesive and a separator containing the same. The present application further relates to a secondary battery, a battery module, a battery pack and a power consuming device. [Background technology]
[0002] In recent years, as the application scope of secondary batteries becomes more and more, secondary batteries are widely used in energy storage power systems such as hydroelectric power plants, thermal power plants, wind power plants, and solar power plants, as well as in multiple fields such as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, and aerospace. With the remarkable development of secondary batteries, the requirements for their cycle performance and safety performance are increasing. However, in the conventional technology, the adhesive has poor adhesion, and the separator is prone to problems such as powder falling and poor adhesion effect with the electrode plate, which restricts the development of secondary battery performance. Therefore, the field needs an adhesive and a separator with better adhesion. Summary of the Invention
[0003] The present application has been made in view of the above problems, and an object of the present application is to provide an adhesive composition, and a separator, a secondary battery, a battery module, a battery pack, and a power consuming device, each of which includes the adhesive composition. The adhesive composition of the present invention can improve the adhesive effect between the ceramic particles and the separator substrate, and between the separator and the electrode plate, and can also improve the cycle performance of the secondary battery.
[0004] To achieve the above object, the present application provides an adhesive, and a separator, a secondary battery, a battery pack, and a power consuming device, each of which includes the adhesive composition.
[0005] A first aspect of the present application provides an adhesive, the adhesive comprising a polymer and ceramic particles modified with a silane coupling agent, the polymer comprising structural units derived from a first class of monomers, a second class of monomers and a third class of monomers, the molar ratio of the first class of monomers, the second class of monomers and the third class of monomers being 50-58:40-44:2-6; The first class of monomers is selected from one or more compounds of formula I: [ka] Wherein, R1 is selected from hydrogen atom and linear or branched C1-6 alkyl group, and R2 is selected from substituted or unsubstituted linear or branched C1-15 alkyl group, C3-6 cycloalkyl group and isobornyl group, in case of substitution, the substituent is selected from hydroxyl group and C1-6 alkyl group; The second class of monomers is selected from one or more compounds of formula II: [ka] wherein R3 is selected from a hydrogen atom and a linear or branched C1-6 alkyl group; The third class of monomers is selected from one or more compounds of formula III: [ka] Wherein R4 is selected from hydrogen atom and linear or branched C1-6 alkyl group, and R5 is selected from hydrogen atom, hydroxy C1-6 alkyl group and C1-6 alkoxy group. The adhesive of the present application has relatively high adhesive strength, reduces and even avoids the "powdering" phenomenon, and improves the cycle performance of secondary batteries.
[0006] In any of the embodiments, R1 is selected from a hydrogen atom and a methyl group, and R2 is selected from a substituted or unsubstituted straight or branched chain C1-6 alkyl group, where if substituted, the substituent is a hydroxyl group, and / or R3 is selected from a hydrogen atom and a methyl group, and / or R4 is selected from a hydrogen atom and a methyl group, and R5 is selected from a hydrogen atom, a hydroxy C1-4 alkyl group, and a C1-4 alkoxy group.
[0007] In any of the embodiments, the first class of monomers is one or more selected from methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, n-propyl acrylate, cyclohexyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, lauryl methacrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, and / or the second class of monomers is acrylonitrile or methacrylonitrile, and / or the third class of monomers is one or more selected from acrylamide, N-methylol acrylamide, and N-butoxymethacrylamide. Furthermore, by selecting the monomers of the above first, second and third classes, the adhesive effect of the adhesive can be improved more effectively, and the cycle capacity retention rate of the battery can be improved.
[0008] In any of the embodiments, the molar ratio of the first type monomer, the second type monomer, and the third type monomer is 50 to 57: 41 to 44: 2 to 6. By adopting a molar ratio in the above range, the adhesive performance of the adhesive can be further improved, and the cycle capacity retention rate of the battery can be improved.
[0009] In any of the embodiments, the weight average molecular weight of the polymer is 60,000 to 120,000, and optionally 63,300 to 118,800. When the weight average molecular weight of the polymer is within the above range, the polymer has suitable fluidity during application of the adhesive and can improve the adhesive effect.
[0010] In any of the embodiments, the average particle size Dv50 of the ceramic particles modified with the silane coupling agent is 200 nm to 980 nm, more preferably 200 nm to 600 nm, and more preferably 330 nm to 550 nm. By controlling the particle size of the ceramic particles within the above range, the ceramic particles are uniformly distributed and are advantageous in being adhered to the separator substrate, and the separator pores are less likely to be blocked.
[0011] In any embodiment, the silane coupling agent is one or more selected from compounds of formula IV: [ka] wherein R6, R7 and R8 are each independently selected from a linear or branched C1-6 alkyl group; R9 is selected from a C2-6 alkenyl group and a C1-6 linear alkyl group; at least one hydrogen atom on the terminal carbon atom of the C1-6 linear alkyl group is substituted with a substituent selected from an amino group, a 2,3-epoxypropoxy group and a methacryloyloxy group; alternatively, R6, R7 and R8 are each independently selected from a methyl group and an ethyl group; and / or R9 is selected from a vinyl group, a 3-aminopropyl group, a 3-(2,3-epoxypropoxy)propyl group and a 3-(methacryloyloxy)propyl group; more alternatively, the silane coupling agent is one or more selected from vinyltriethoxysilane, 3-aminopropyltriethoxysilane, 3-(2,3-epoxypropoxy)propyltrimethoxysilane and 3-(methacryloyloxy)propyltrimethoxysilane. The ceramic particles modified with the above silane coupling agent can be selected to improve the adhesive effect and further improve the capacity retention.
[0012] In any of the embodiments, the weight ratio of the ceramic particles to the silane coupling agent is 97.5-99.9:0.1-2.5, more preferably 98.0-99.9:0.1-2.0, and even more preferably 98.2-99.4:0.6-1.8. By setting the weight ratio of the ceramic particles to the silane coupling agent within the above range, it is advantageous to realize the effect of improving the adhesive strength and cycle performance.
[0013] In any of the embodiments, the weight ratio of the polymer to the ceramic particles is 40-90:10-60, and optionally 50-80:20-50. When the weight ratio of the polymer to the ceramic particles is within the above content range, "powder falling" is unlikely to occur, and it is advantageous for improving the battery cycle performance.
[0014] In either embodiment, the polymer coats the ceramic particles, thus advantageously reducing or avoiding pore clogging and achieving improved heat resistance performance and good adhesion.
[0015] A second aspect of the present application provides a separator, the separator comprising a base layer and a coating layer disposed on at least one surface of the base layer, the coating layer comprising the adhesive of the first aspect of the present application. The separator of the present application has good chemical and mechanical stability, good adhesion between the separator and a positive electrode plate, and is advantageous in improving the cycle performance of a battery.
[0016] A third aspect of the present application provides a secondary battery, the secondary battery comprising the adhesive of the first aspect of the present application or the separator according to the second aspect of the present application.
[0017] A fourth aspect of the present application provides a battery module, the battery module including the secondary battery of the third aspect of the present application.
[0018] A fifth aspect of the present application provides a battery pack, the battery pack including the battery module of the fourth aspect of the present application.
[0019] A sixth aspect of the present application provides a power consumption device, the power consumption device including at least one selected from the secondary battery of the third aspect of the present application, the battery module of the fourth aspect of the present application, or the battery pack of the fifth aspect of the present application.
[0020] The adhesive of the present application has good adhesive performance and enhances the cycle performance of secondary batteries. [Brief description of the drawings]
[0021] [Figure 1] 1 is a schematic diagram of a secondary battery according to an embodiment of the present application; [Diagram 2] FIG. 2 is an exploded view of the secondary battery according to the embodiment of the present application shown in FIG. [Diagram 3] 1 is a schematic diagram of a battery module according to an embodiment of the present application; [Figure 4] 1 is a schematic diagram of a battery pack according to an embodiment of the present application; [Diagram 5] FIG. 5 is an exploded view of the battery pack according to the embodiment of the present application shown in FIG. 4. [Figure 6] 1 is a schematic diagram of a power consuming device in which a secondary battery according to an embodiment of the present application is used as a power source; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] Hereinafter, with appropriate reference to the drawings, embodiments specifically disclosing the adhesive, separator, secondary battery, battery module, battery pack, and electric device of the present application will be described in detail. However, unnecessary detailed description may be omitted. For example, detailed description of well-known matters and duplicated description of structures that are actually the same may be omitted. This is to avoid the following description becoming unnecessarily long and to allow those skilled in the art to easily understand. Note that the drawings and the following description are provided to allow those skilled in the art to fully understand the present application, and are not intended to limit the subject matter described in the claims.
[0023] The "ranges" disclosed in this application are defined in the form of lower and upper limits, and a given range is defined by selecting one lower limit and one upper limit, and the selected lower and upper limits define the boundaries of the particular range. Such defined ranges may be inclusive or exclusive of the extreme values, and may be arbitrarily combined, i.e., any lower limit may be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a particular parameter, it is understood that ranges of 60-110 and 80-120 are also envisaged. However, if 1 and 2 are listed as minimum range values, and 3, 4, and 5 are listed as maximum range values, the ranges 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5 are all envisaged. In this application, unless otherwise specified, the numerical range "ab" represents a shorthand representation of any combination of real numbers from a to b, where a and b are both real numbers. For example, the numerical range "0-5" represents a list of all real numbers between "0-5" already listed in this specification, and "0-5" is just a shorthand representation of combinations of these numbers. Also, expressing a parameter as an integer ≧2 is equivalent to disclosing that the parameter is, for example, the integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0024] Unless otherwise stated, all the embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0025] Unless otherwise stated, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0026] Unless otherwise stated, all steps in this application may be performed in sequence or randomly, and preferably in sequence. For example, the method includes steps (a) and (b) to mean that the method may include steps (a) and (b) performed in sequence, or may include steps (b) and (a) performed in sequence. For example, the method mentioned above may further include step (c) to mean that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), may include steps (a), (c) and (b), may include steps (c), (a) and (b), etc.
[0027] Unless otherwise stated, the terms "comprise" and "include" referred to in this application may be open ended or closed ended. For example, the terms "comprise" and "include" may further include or include other ingredients not listed, or may include or include only the listed ingredients.
[0028] Unless otherwise stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, "A or B" is satisfied if A is true (or exists) and B is false (or does not exist), if A is false (or does not exist) but B is true (or exists), or if both A and B are true (or exist).
[0029] In recent years, as the application range of secondary batteries becomes wider, secondary batteries are widely used in energy storage power systems such as hydroelectric power plants, thermal power plants, wind power plants, and solar power plants, as well as in multiple fields such as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, and aerospace. With the remarkable development of secondary batteries, the requirements for their energy density, cycle performance, and safety performance are increasing. The separator, as one of the important components of secondary batteries, has become the focus of research and improvement in this field. In order to improve the heat resistance of the separator, the currently commonly adopted method is to apply a coating containing ceramic particles (e.g., inorganic oxide particles, e.g., silicon dioxide particles) and a polymer adhesive on the surface of the separator substrate to suppress the thermal shrinkage of the separator when exposed to high temperatures. However, the conventional polymer adhesive has various problems. It has low compatibility with ceramic particles, is prone to "powdering", the adhesion state between the coating and the substrate cannot be effectively maintained for a long period during the manufacture and use of the battery, and the adhesion force between the separator and the electrode plate is low, which affects the cycle performance of the secondary battery.
[0030] Therefore, the art needs an adhesive that can improve the above problems. Therefore, the present application provides an adhesive composition, which includes a polymer that performs adhesive function and ceramic particles modified with a silane coupling agent that improves safety performance, achieves good adhesive effect, and improves capacity retention.
[0031] glue In one embodiment of the present application, the present application proposes an adhesive, the adhesive comprising a polymer and ceramic particles modified with a silane coupling agent, the polymer comprising structural units derived from a first class of monomers, a second class of monomers and a third class of monomers, the molar ratio of the first class of monomers, the second class of monomers and the third class of monomers being 50-58:40-44:2-6; The first class of monomers is selected from one or more compounds of formula I: [ka] Wherein, R1 is selected from hydrogen atom and linear or branched C1-6 alkyl group, and R2 is selected from substituted or unsubstituted linear or branched C1-15 alkyl group, C3-6 cycloalkyl group and isobornyl group, in case of substitution, the substituent is selected from hydroxyl group and C1-6 alkyl group; The second class of monomers is selected from one or more compounds of formula II: [ka] wherein R3 is selected from a hydrogen atom and a linear or branched C1-6 alkyl group; The third class of monomers is selected from one or more compounds of formula III: [ka] wherein R4 is selected from a hydrogen atom and a straight or branched C1-6 alkyl group, and R5 is selected from a hydrogen atom, a hydroxy C1-6 alkyl group, and a C1-6 alkoxy group.
[0032] The adhesive of the present application has a relatively high adhesive strength, reduces or even avoids the phenomenon of "powdering" of ceramic particles, improves the adhesive effect between the separator and the electrode plate (especially the positive electrode plate), and improves the cycle performance of the secondary battery.
[0033] The first type of monomer is an acrylate monomer, which can improve the anti-swelling ability of the polymer, and as a flexible monomer chain segment in the molecular chain segment, can adjust the glass transition temperature of the polymer and improve the fluidity of the adhesive when applied, which is advantageous for exerting a good adhesive effect. The second type of monomer is an acrylonitrile monomer, which has a strongly polar cyano group, which is advantageous for improving ion conductivity and improving cycle performance. The third type of monomer is an acrylamide monomer, which plays the role of adjusting molecular weight. The molar ratio of the above three types of monomers needs to be controlled within the above range, which can control the molecular weight and glass transition temperature of the polymer, thereby improving the adhesive performance.
[0034] The silane coupling agent is firmly bonded to the ceramic particles, thereby improving the compatibility of the inorganic particles in an organic environment (e.g., high dispersibility), and can further crosslink with the polymer and separator base layer material, improving the adhesive effect between the adhesive and the separator and electrode plates.
[0035] In this specification, "ceramic particles modified with a silane coupling agent" may also be referred to as ceramic particles that have been coated or surface-modified with a silane coupling agent, and means that the coupling agent molecules are bonded to the ceramic particles by forming covalent bonds or hydrogen bonds between hydroxyl groups generated after hydrolysis of the coupling agent and active groups on the surface of the ceramic particles.
[0036] In some embodiments, R1 is selected from a hydrogen atom and a methyl group, and R2 is selected from a substituted or unsubstituted linear or branched C1-6 alkyl group, where if substituted, the substituent is a hydroxyl group, and / or R3 is selected from a hydrogen atom and a methyl group, and / or R4 is selected from a hydrogen atom and a methyl group, and R5 is selected from a hydrogen atom, a hydroxy C1-4 alkyl group, and a C1-4 alkoxy group.
[0037] In some embodiments, the first class of monomers is one or more selected from methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, n-propyl acrylate, cyclohexyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, lauryl methacrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate. In some embodiments, the second class of monomers is acrylonitrile or methacrylonitrile. In some embodiments, the third class of monomers is one or more selected from acrylamide, N-methylolacrylamide, and N-butoxymethacrylamide.
[0038] Furthermore, by selecting the monomers of the above first, second and third classes, the adhesive effect of the adhesive can be improved more effectively, and the cycle capacity retention rate of the battery can be improved.
[0039] In some embodiments, the molar ratio of the first type monomer to the second type monomer to the third type monomer is 50-57:41-44:2-6. By adopting a molar ratio in the above range, the adhesive performance of the adhesive can be further improved, and the cycle capacity retention rate of the battery can be improved.
[0040] In some embodiments, based on the total molar amount of the first, second and third class monomers, the molar percentage content of the first class monomers is 50-58 mol%, alternatively 50-57 mol%, alternatively the molar percentage content of the first class monomers is 50 mol%, 51 mol%, 52 mol%, 53 mol%, 54 mol%, 55 mol%, 56 mol%, 57 mol%, or 58 mol%, or any of the above values. In some embodiments, based on the total molar amount of the first, second and third class monomers, the molar percentage content of the second class monomers is 40-44 mol%, alternatively 41-44 mol%, alternatively the molar percentage content of the second class monomers is 40 mol%, 41 mol%, 42 mol%, 43 mol%, or 44 mol%, or any of the above values. In some embodiments, based on the total molar amount of the first type monomer, the second type monomer, and the third type monomer, the molar percentage content of the third type monomer is 2-6 mol%, alternatively, the molar percentage content of the third type monomer is 2 mol%, 3 mol%, 4 mol%, 5 mol%, or 6 mol%, or within a range consisting of any and both of the foregoing values.
[0041] In some embodiments, the weight average molecular weight of the polymer is 60,000 to 120,000, optionally 63,300 to 118,800. When the weight average molecular weight of the polymer is within the above range, the polymer has suitable fluidity during application of the adhesive and can improve the adhesive effect.
[0042] In some embodiments, the ceramic particles may be selected from conventional materials in the art. In some embodiments, the ceramic particles are selected from aluminum oxide, boehmite, titanium dioxide, and silicon dioxide. The selection of these materials can improve the heat resistance of the separator and improve safety.
[0043] In some embodiments, the average particle size Dv50 of the ceramic particles modified with the silane coupling agent is 200 nm to 980 nm, and optionally the average particle size Dv50 is 330 nm, 460 nm, 550 nm, 590 nm, 780 nm, or 980 nm, or any of the above values. Optionally, the average particle size Dv50 is 200 nm to 600 nm, and more preferably 330 nm to 590 nm, and more preferably 330 nm to 550 nm. By controlling the particle size of the ceramic particles within the above range, the ceramic particles are advantageously uniformly distributed and adhered to the separator substrate, and are less likely to clog the separator pores, have high adhesion, and have good capacity retention.
[0044] In some embodiments, the silane coupling agent is one or more selected from compounds of formula IV: [ka] wherein R6, R7, and R8 are each independently selected from a linear or branched C1-6 alkyl group, and R9 is selected from a C2-6 alkenyl group and a C1-6 linear alkyl group, wherein at least one hydrogen atom on the terminal carbon atom of the C1-6 linear alkyl group is substituted with a substituent selected from an amino group, a 2,3-epoxypropoxy group, and a methacryloyloxy group. In some embodiments, the C2-6 alkenyl group is a terminal alkenyl group. In some embodiments, R6, R7, and R8 are each independently selected from a linear or branched C1-4 alkyl group, and optionally R6, R7, and R8 are each independently selected from a methyl group, an ethyl group, an n-propyl group, and an isopropyl group, and further optionally R6, R7, and R8 are each independently selected from a methyl group and an ethyl group. In some embodiments, R9 is selected from C2-4 alkenyl and C1-4 linear alkyl groups, optionally C2-4 terminal alkenyl and C1-4 linear alkyl groups, with one hydrogen atom on the terminal carbon atom of the C1-4 linear alkyl group being replaced with a substituent selected from amino, 2,3-epoxypropoxy and methacryloyloxy. In some embodiments, optionally, R6, R7 and R8 are each independently selected from methyl and ethyl, and R9 is selected from vinyl, 3-aminopropyl, 3-(2,3-epoxypropoxy)propyl and 3-(methacryloyloxy)propyl. By selecting ceramic particles modified with the above-mentioned silane coupling agent (which may also be called a coating treatment or surface modification treatment for ceramic particles), a covalent bond or hydrogen bond is formed between the hydroxyl group generated after hydrolysis of the coupling agent and the active group on the surface of the ceramic particles, and the active group of the silane coupling agent itself reacts with the polymer and the separator substrate to perform a "bridge bonding" function, thereby improving the adhesion effect and improving the capacity retention rate.
[0045] In some embodiments, optionally, R6, R7 and R8 are each independently selected from methyl and ethyl, and R9 is selected from vinyl, 3-aminopropyl, 3-(2,3-epoxypropoxy)propyl and 3-(methacryloyloxy)propyl. In some embodiments, the silane coupling agent is one or more selected from vinyltriethoxysilane, 3-aminopropyltriethoxysilane, 3-(2,3-epoxypropoxy)propyltrimethoxysilane and 3-(methacryloyloxy)propyltrimethoxysilane, which can obtain good adhesion and ideal capacity retention.
[0046] In some embodiments, the weight ratio of the ceramic particles to the silane coupling agent is 97.5-99.9:0.1-2.5, more preferably 98.0-99.9:0.1-2.0, and more preferably 98.2-99.4:0.6-1.8. By setting the weight ratio of the ceramic particles to the silane coupling agent within the above range, the surface of the ceramic particles is quickly and effectively covered with the silane coupling agent, thereby improving dispersibility, but the coupling agent itself does not crosslink or coagulate, which is advantageous in realizing the effect of improving adhesion and cycle performance.
[0047] In some embodiments, the weight ratio of the polymer to the ceramic particles is 40-90:10-60, and optionally 50-80:20-50. When the weight ratio of the polymer to the ceramic particles is within the above content range, "powder falling" is unlikely to occur, the heat resistance of the separator is good, and the electrolyte permeation and electrolyte absorption and retention capabilities are good, which is advantageous for improving the battery cycle performance.
[0048] In some embodiments, the polymer coats the ceramic particles. Before application, the polymer is coated on the ceramic particles, thereby reducing or avoiding the particles from falling into the separator pores and causing clogging of the pores, and ensuring that the adhesive composition is evenly applied on the substrate with an ideal blending ratio, thereby achieving improved heat resistance performance and good adhesion effect.
[0049] Separator Another aspect of the present application provides a separator including a base layer and a coating layer disposed on at least one surface of the base layer, the coating layer including the adhesive of the present application.
[0050] The present application is not particularly limited to the material type of the separator base layer, and any known porous structure base layer having good chemical stability and mechanical stability may be selected.
[0051] In some embodiments, the material of the separator base layer may be at least one selected from glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator may be a monolayer film or a multilayer composite film, and is not particularly limited. When the separator is a multilayer composite film, the materials of each layer may be the same or different, and is not particularly limited.
[0052] Secondary battery, battery module, battery pack and power consuming device A third aspect of the present application provides a secondary battery, the secondary battery including the adhesive of the present application and / or the separator of the present application.
[0053] A fourth aspect of the present application provides a battery module, the battery module including the secondary battery of the third aspect.
[0054] A fifth aspect of the present application provides a battery pack, the battery pack including the battery module of the fourth aspect.
[0055] A sixth aspect of the present application provides a power consumption device, the power consumption device including at least one selected from the secondary battery of the third aspect, the battery module of the fourth aspect, and the battery pack of the fifth aspect.
[0056] The secondary battery, the battery module, the battery pack, and the power consuming device of the present application will be described below with appropriate reference to the drawings.
[0057] In one embodiment of the present application, a secondary battery is provided, in some embodiments, the secondary battery is a lithium ion secondary battery.
[0058] Generally, a secondary battery includes a positive electrode plate, a negative electrode plate, an electrolyte, and a separator. During charging and discharging of the battery, active ions shuttle between the positive electrode plate and the negative electrode plate to be absorbed and released. The electrolyte functions to conduct ions between the positive electrode plate and the negative electrode plate. The separator is installed between the positive electrode plate and the negative electrode plate, and mainly functions to prevent a short circuit between the positive and negative electrodes, while allowing ions to pass through.
[0059] [Positive electrode plate] The positive electrode plate includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, the positive electrode film layer including the positive electrode active material of the first aspect of the present application.
[0060] For example, a positive electrode current collector has two opposing surfaces in the thickness direction of the positive electrode current collector, and a positive electrode film layer is disposed on either one or both of the two opposing surfaces of the positive electrode current collector.
[0061] In some embodiments, the positive electrode current collector may be a metal foil sheet or a composite current collector. For example, an aluminum foil may be used as the metal foil sheet. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base layer. The composite current collector may be formed by forming a metal material (such as aluminum, aluminum alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0062] In some embodiments, the positive electrode active material may be any positive electrode active material known in the art for use in batteries. For example, the positive electrode active material may include at least one of lithium-containing phosphates with an olivine structure, lithium transition metal oxides and their respective modified compounds, sodium transition metal oxides, polyanion-type compounds, and Prussian blue-based compounds. However, the present application is not limited to these materials, and other conventional materials that can be used as positive electrode active materials in batteries may be used. These positive electrode active materials may be used alone or in combination of two or more. Here, examples of lithium transition metal oxides include lithium cobalt oxide (e.g., LiCoO2), lithium nickel oxide (e.g., LiNiO2), lithium manganese oxide (e.g., LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (e.g., LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM 333 (may be abbreviated as LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM 523 (may be abbreviated as LiNi 0.5 Co 0.25 Mn 0.25 O2(NCM 211 (may be abbreviated as LiNi0.6 Co 0.2 Mn 0.2 O2 (which may be abbreviated as NCM 622 ), LiNi 0.8 Co 0.1 Mn 0.1 O2 (which may be abbreviated as NCM 811 ))), lithium nickel cobalt aluminum oxide (for example, LiNi 0.85 Co 0.15 Al 0.05 O2) and may include, but are not limited to, at least one of its modified compounds. Examples of olivine-structured lithium-containing phosphates include lithium iron phosphate (for example, LiFePO4 (which may be abbreviated as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (for example, LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium manganese iron phosphate, and a composite material of lithium manganese iron phosphate and carbon, and may include, but are not limited to, at least one of them.
[0063] In some embodiments, in the sodium transition metal oxide, the transition metal may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce. The sodium transition metal oxide is, for example, Na x M y O2, where M is one or more of Ti, V, Mn, Co, Ni, Fe, Cr, and Cu, and 0 < x ≤ 1, 0.5 < y ≤ 1.5. In some embodiments, the positive electrode active material may employ Na 0.88 Cu 0.24 Fe 0.29 Mn 0.47 O2.
[0064] In some embodiments, the polyanion-type compound may be a kind of compound having sodium ions, transition metal ions, and tetrahedral (YO4) n- anion units. The transition metal may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce, Y may be at least one of P, S, and Si, and n is (YO4)n- Represents the valence of.
[0065] In some embodiments, the polyanionic compound includes sodium ions, transition metal ions, tetrahedral (YO4) n- The anion unit may be a compound having a halogen anion. The transition metal may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce, Y may be at least one of P, S, and Si, and n is (YO4) n- and the halogen may be at least one of F, Cl, and Br.
[0066] In some embodiments, the polyanionic compound is a sodium ion, tetrahedral (YO4) n- Anionic unit, polyhedral unit (ZO y ) m+ and an optional halogen anion. Y may be at least one of P, S, and Si, and n is (YO4) n- Z represents a transition metal and may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce, and m represents a valence of (ZO y ) m+ and the halogen may be at least one of F, Cl, and Br.
[0067] In some embodiments, the polyanionic compounds include, for example, NaFePO4, Na3V2(PO4)3, NaM'PO4F (where M' is one or more of V, Fe, Mn, and Ni), and Na3(VO y )2(PO4)2F 3-2y At least one of (0≦y≦1).
[0068] In some embodiments, the Prussian blue based compound contains sodium ions, transition metal ions, and cyanide ions (CN -The transition metal may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce. The Prussian blue compound may be, for example, Na a Me b Me' c (CN)6, where Me and Me' are each independently at least one of Ni, Cu, Fe, Mn, Co, and Zn; <a≦2、0<b<1、0<c<1である。
[0069] In some embodiments, the positive electrode membrane layer further optionally includes an adhesive, which may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0070] In some embodiments, the positive electrode film layer further optionally includes a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0071] In some embodiments, the positive electrode plate may be manufactured in the following manner: the components for manufacturing the positive electrode plate, such as the positive electrode active material, the conductive agent, the adhesive, and any other components, are dispersed in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry, and the positive electrode slurry is coated on a positive electrode current collector, and the positive electrode plate can be obtained after processes such as drying and cold pressing.
[0072] [Negative electrode plate] The negative electrode plate includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, the negative electrode film layer including a negative electrode active material.
[0073] For example, the negative electrode current collector has two opposing surfaces in the thickness direction of the negative electrode current collector, and the negative electrode film layer is disposed on either one or both of the two opposing surfaces of the negative electrode current collector.
[0074] In some embodiments, the negative electrode current collector may be a metal foil sheet or a composite current collector. For example, a copper foil may be used as the metal foil sheet. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (such as copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0075] In some embodiments, the negative electrode active material may be a negative electrode active material for batteries known in the art. For example, the negative electrode active material may include at least one of artificial graphite, natural graphite, soft carbon, hard carbon, silicone-based materials, tin-based materials, and lithium titanate. The silicone-based material may be selected from at least one of silicone monomers, silicone oxides, silicone carbon composites, silicone nitrogen composites, and silicone alloys. The tin-based material may be selected from at least one of monomeric tin, stannic acid compounds, and tin alloys. However, the present application is not limited to these materials, and other conventional materials that can be used as a battery negative electrode active material may be used. These negative electrode active materials may be used alone or in combination of two or more.
[0076] In some embodiments, the negative electrode membrane layer further optionally comprises an adhesive, which may be selected from at least one of styrene butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0077] In some embodiments, the negative electrode film layer further optionally comprises a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0078] In some embodiments, the negative electrode membrane layer optionally further comprises other auxiliary agents, such as a thickening agent (eg, sodium carboxymethylcellulose (CMC-Na)).
[0079] In some embodiments, the negative electrode plate may be manufactured in the following manner: components for manufacturing the negative electrode plate, such as a negative electrode active material, a conductive agent, an adhesive, and any other components, are dispersed in a solvent (e.g., deionized water) to form a negative electrode slurry, and the negative electrode slurry is coated on a negative electrode current collector. After processes such as drying and cold pressing, the negative electrode plate can be obtained.
[0080] [Electrolyte] The electrolyte serves to conduct ions between the positive and negative electrodes. The present application is not specifically limited to the type of electrolyte, which can be selected according to need. For example, the electrolyte may be liquid, gel, or all solid.
[0081] In some embodiments, the electrolyte is an electrolytic solution, the electrolytic solution including an electrolyte salt and a solvent.
[0082] In some embodiments, the electrolyte salt is selected from the group consisting of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluoro(oxalato)borate, lithium bis(oxalato)borate, lithium difluorobis(oxalato)phosphate, and lithium tetrafluoro(oxalato)phosphate, sodium hexafluorophosphate (NaPF), sodium hexafluoroborate (NaBF), NaN(SOF) (abbreviated as NaFSI), NaClO, NaAsF, NaB(CO) (abbreviated as NaBOB), NaBF(CO) (abbreviated as NaDFOB), NaN(SOR F )2 and NaN(SO2F)(SO2R F ), where R F is C b F 2b+1 where b is an integer in the range of 1-10, optionally an integer in the range of 1-3, and further optionally R F is -CF3, -C2F5 or -CF2CF2CF3.
[0083] In some embodiments, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, ethyl methyl sulfone, and diethyl sulfone.
[0084] In some embodiments, the electrolyte solution further optionally includes additives. For example, the additives may include an anode film-forming additive, a cathode film-forming additive, and may further include additives that can improve some performance of the battery, such as an additive that improves the overcharge performance of the battery, an additive that improves the high temperature or low temperature performance of the battery, etc.
[0085] In some embodiments, the positive plates, negative plates and separators can be fabricated into an electrode assembly by a winding process or a lamination process.
[0086] [Exterior body] In some embodiments, the secondary battery may include an exterior body for packaging the positive electrode plate, the negative electrode plate and the electrolyte. As an example, the positive electrode plate, the negative electrode plate and the separator may be stacked or wound to form a stacked structure battery core or a wound structure battery core, and the battery core is packaged in the exterior body, and the electrolyte employs the electrolyte solution described in the first aspect of the present application, and the electrolyte solution is permeated into the battery core. The number of battery cores in the secondary battery may be one or more, and can be adjusted according to demand.
[0087] In one embodiment, the present application provides an electrode assembly. In some embodiments, the positive electrode plate, the negative electrode plate and the separator can be fabricated into an electrode assembly by a winding process or a lamination process. An exterior body can be used to package the electrode assembly and the electrolyte.
[0088] In some embodiments, the exterior of the secondary battery may be a pouch, such as a bag-shaped pouch. The material of the pouch may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc. In some embodiments, the exterior of the secondary battery may be a hard case, such as a hard plastic case, an aluminum case, a steel case, etc.
[0089] The present application is not particularly limited to the shape of the secondary battery, which may be cylindrical, rectangular, or any other shape. For example, FIG. 1 shows a secondary battery 5 with a rectangular structure as an example.
[0090] In some embodiments, referring to FIG. 2, the exterior body may include a case 51 and a cover plate 53. Here, the case 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate surround and form a receiving cavity. The case 51 has an opening communicating with the receiving cavity, and the cover plate 53 may be installed on the opening to seal the receiving cavity. The positive electrode plate, the negative electrode plate and the separator may form an electrode assembly 52 by a winding process or a stacking process. The electrode assembly 52 is packaged in the receiving cavity. An electrolyte is infiltrated into the electrode assembly 52. The number of electrode assemblies 52 included in the secondary battery 5 may be one or more, and those skilled in the art may select it according to actual needs.
[0091] In some embodiments, the secondary batteries can be assembled into a battery module, and the number of secondary batteries included in the battery module can be one or more, with the specific number being selectable by one skilled in the art depending on the application and capacity of the battery module.
[0092] Fig. 3 shows an example of a battery module 4. Referring to Fig. 3, in the battery module 4, the multiple secondary batteries 5 may be arranged in sequence along the longitudinal direction of the battery module 4. Of course, they may be arranged in any other manner. Furthermore, the multiple secondary batteries 5 may be fixed by fasteners.
[0093] Optionally, the battery module 4 may further include a housing having an accommodating space, and the multiple secondary batteries 5 are accommodated in the accommodating space.
[0094] In some embodiments, the battery modules may be further assembled into a battery pack, and the number of battery modules included in the battery pack may be one or more, and the specific number can be selected by one skilled in the art according to the application and capacity of the battery pack.
[0095] 4 and 5 show an example of a battery pack 1. Referring to Fig. 4 and Fig. 5, the battery pack 1 may include a battery box and a plurality of battery modules 4 installed in the battery box. The battery box includes an upper housing 2 and a lower housing 3, and the upper housing 2 is covered by the lower housing 3 to form a sealed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.
[0096] The present application further provides a power consuming device, the power consuming device including at least one of the secondary battery, the battery module, or the battery pack according to the present application. The secondary battery, the battery module, or the battery pack may be used as a power source for the power consuming device, or may be used as an energy storage unit for the power consuming device. The power consuming device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0097] The power consumption device can be a secondary battery, a battery module, or a battery pack depending on its usage demand.
[0098] 6 shows an example of a power consuming device, such as a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. A battery pack or a battery module can be employed to meet the demand for high power and high energy density of the secondary battery of the power consuming device.
[0099] Other exemplary devices may be mobile phones, tablet computers, notebook computers, etc. These devices are generally required to be thin and can employ secondary batteries as their power source.
[0100] Working Example The following is a description of the examples of the present application. The examples described below are illustrative and are only for interpreting the present application, and should not be understood as limitations on the present application. In the examples, if no specific technique or condition is specified, the technique or condition is performed according to the technique or condition described in the literature in the field, or according to the product specifications. The reagents or equipment used are not specified by manufacturer, and are all ordinary products that are commercially available. EXAMPLES
[0101] 1. Polymer Production Manufacturing Example 1 At room temperature, 60.92g of methyl acrylate, 33.04g of acrylonitrile and 6.04g of acrylamide were weighed according to a molar ratio of 50:44:6, and added to a 500mL four-neck flask equipped with a mechanical stirrer, a thermometer and a condenser pipe, and then 3g of sodium lauryl sulfate emulsifier, 1g of ammonium persulfate initiator and 120g of deionized water were added, and emulsified by stirring at a rotation speed of 1600 rpm for 30 minutes, and then heated to 75°C under nitrogen protection and reacted for 4 hours, and the pH value was adjusted to 6-8, and the temperature was immediately lowered to below 40°C and discharged to obtain polymer 1.
[0102] Manufacturing Examples 2 to 5 The production steps of Production Examples 2 to 5 are the same as those of Production Example 1, but the difference is that the molar ratios of the three types of monomers are 51:43:6, 52:42:6, 53:41:6 and 54:40:6, respectively, and the total mass of the three types of monomers is 100 g, to obtain polymers 2 to 5.
[0103] Manufacturing Examples 6-10 In Preparation 6, 69.71g of n-butyl acrylate, 24.90g of acrylonitrile and 5.39g of N-methylolacrylamide were weighed out at room temperature according to a molar ratio of 51:44:5, and the other steps were the same as Preparation 1 to obtain Polymer 6.
[0104] In Preparation Examples 7 to 10, the molar ratios of the three monomers were 52:43:5, 53:42:5, 54:41:5, and 55:40:5, respectively, and the total mass of the three monomers was 100 g. The other steps were the same as in Preparation Example 1, and polymers 7 to 10 were obtained.
[0105] Manufacturing Examples 11-15 In Preparation 11, 68.42g ethyl methacrylate, 26.91g acrylonitrile and 4.66g N-methylolacrylamide were weighed out at room temperature according to a molar ratio of 52:44:4, and other steps were the same as Preparation 1 to obtain Polymer 11.
[0106] In Production Examples 12 to 15, the molar ratios of the three types of monomers were 53:43:4, 54:42:4, 55:41:4, and 56:40:4, respectively, and the total mass of the three types of monomers was 100 g. The other steps were the same as in Production Example 1, and polymers 12 to 15 were obtained.
[0107] Manufacturing Examples 16-20 In Preparation 16, 67.94g of 2-hydroxyethyl methacrylate, 29.08g of methacrylonitrile and 2.99g of N-butoxymethacrylamide were weighed out at room temperature according to a molar ratio of 53:44:3, and the other steps were the same as Preparation 1 to obtain Polymer 16.
[0108] In Production Examples 17 to 20, the molar ratios of the three types of monomers were 54:43:3, 55:42:3, 56:41:3, and 57:40:3, respectively, and the total mass of the three types of monomers was 100 g. The other production steps were the same as those in Production Example 1, and polymers 17 to 20 were obtained.
[0109] Manufacturing Examples 21-25 In Preparation Example 21, 70.44g of 2-hydroxypropyl methacrylate, 26.71g of methacrylonitrile and 2.85g of N-butoxymethacrylamide were weighed out at room temperature according to a molar ratio of 54:44:2, and other preparation steps were the same as Preparation Example 1 to obtain Polymer 21.
[0110] In Production Examples 22 to 25, the molar ratios of the three types of monomers were 55:43:2, 56:42:2, 57:41:2, and 58:40:2, respectively, and the total mass of the three types of monomers was 100 g. The other production steps were the same as those in Production Example 1, and polymers 22 to 25 were obtained.
[0111] Manufacturing Example 26 In Preparation 26, 75.13g of cyclohexyl acrylate, 20.88g of acrylonitrile, and 4.00g of acrylamide were weighed out at room temperature according to a molar ratio of 52:42:6, and other preparation steps were the same as those in Preparation 1 to obtain Polymer 26.
[0112] Manufacturing Example 27 In Preparation Example 27, 80.07g isobornyl methacrylate, 16.95g methacrylonitrile, 2.98g N-butoxymethacrylamide were weighed out at room temperature according to a molar ratio of 57:40:3, and other preparation steps were the same as Preparation Example 1 to obtain Polymer 27.
[0113] Comparative Manufacturing Example 1 At room temperature, 69.50g methyl acrylate, 22.85g acrylonitrile and 7.65g acrylamide were weighed according to a molar ratio of 60:32:8, and the other steps were the same as in Preparation Example 1 to obtain Polymer C1.
[0114] Comparative Manufacturing Example 2 At room temperature, 74.42g of 2-hydroxyethyl methacrylate and 25.58g of methacrylonitrile were weighed out according to a molar ratio of 60:40, and the other steps were the same as in Preparation Example 1 to obtain Polymer C2.
[0115] The weight average molecular weights of Polymer 1-26 obtained in the above Production Example and Comparative Production Example and Comparative Polymer 1 were measured by gel permeation chromatography.
[0116] Table 1 shows the monomers and their molar ratios in the above Production Examples 1-25 and Comparative Production Example 1-2, as well as the weight average molecular weights of the final polymers obtained.
[0117] [Table 1] TIFF0007635428000010.tif237168TIFF0007635428000011.tif109168
[0118] 2. Preparation of silicon dioxide particles modified with silane coupling agents A mixed liquid was prepared with a mass ratio of water:ethyl alcohol:silane coupling agent of 8:72:20, and silicon dioxide particles were added to a stirrer and heated to 60-70°C. The mixed liquid was slowly added dropwise until the mass ratio of silicon dioxide particles to the mixed liquid finally became as shown in Table 2 below. After the addition was completed, stirring was continued for 2-3 hours to obtain a mixed material. The mixed material was dried at 120°C for 2 hours to obtain silicon dioxide particles modified with a silane coupling agent.
[0119] A laser particle size analyzer was used to measure the average particle size Dv50 of the silicon dioxide particles modified with the silane coupling agent using deionized water as a dispersant, as shown in Table 2 below.
[0120] 3. Preparation of adhesive composition and performance testing Example 1 1. Preparation of adhesive composition According to the mass ratio of polymer and silicon dioxide particles modified with silane coupling agent of 75:25, 250g of silicon dioxide particles modified with silane coupling agent and 1kg of deionized water are added to 750g of polymer 1 obtained in Preparation Example 1, and stirred for 1 hour under room temperature conditions, sprayed and dried, and the polymer-modified silicon dioxide particles are coated, and then ball milled to obtain an adhesive. The silane coupling agent used is vinyltriethoxysilane, and the average particle size Dv50 of the produced silicon dioxide particles modified with silane coupling agent is 460nm.
[0121] 2. Manufacturing of separators A commercially available PP-PE copolymer microporous film (Model No. 20 from Zhuogao Electronics Technology Co., Ltd.) with a thickness of 20 μm and an average pore size of 80 nm is used as the substrate. The coating composition prepared above is uniformly stirred and mixed in N-methylpyrrolidone (NMP) to obtain a slurry (solid content is 20%). The slurry is uniformly coated on two surfaces of the substrate, and the organic solvent is dried to remove, so that the coating density of the coating composition on the substrate is 0.5 g / m 2 Thus, a separator was obtained.
[0122] 3. Manufacturing of positive electrode plates Polyvinylidene fluoride (PVDF), lithium iron phosphate (LFP), conductive carbon black, and N-methylpyrrolidone (NMP) were thoroughly and uniformly mixed in a mass ratio of 1.2:58.38:0.42:40 to produce a positive electrode slurry. 2 The aluminum foil positive electrode current collector was uniformly coated with the carrier in an amount of 0.1 to 1000g, and then dried, cold pressed, and slit to obtain a positive electrode plate.
[0123] 4. Manufacturing of negative electrode plates Artificial graphite, conductive agent acetylene black, adhesive styrene butadiene rubber (SBR), and thickener sodium carboxymethylcellulose (CMC-Na) were added to deionized water in a mass ratio of 96.2:1.0:1.6:1.2, and thoroughly and uniformly mixed to prepare anode slurry (solid content 63%). This anode slurry was prepared at 98 g / m2 The negative electrode current collector copper foil was coated with the carrier in an amount of 0.1g / g, and then dried, cold pressed, and slit to obtain a negative electrode plate.
[0124] 5. Electrolyte Production At 25°C, ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain a mixed solvent, and LiPF6 is dissolved in the mixed solvent to obtain an electrolyte, in which the concentration of LiPF6 is 1 mol / L.
[0125] 6. Secondary battery manufacturing The positive electrode plate, separator, and negative electrode plate were stacked in this order, wound, and pre-press molded (the separator was bonded to the electrode plate during this period) to obtain an electrode assembly. The electrode assembly was then placed in an outer casing, and the above-prepared electrolyte solution was added. After going through processes such as packaging, standing, chemical formation, and aging, a secondary battery was obtained.
[0126] Example 2 According to the weight ratio of polymer and silane coupling agent modified silicon dioxide of 60:40, 400g of modified silicon dioxide particles and 1kg of deionized water are added to 600g of the polymer of Preparation Example 11, and the mixture is stirred at room temperature for 1 hour, sprayed and dried, and then ball milled to obtain an adhesive. Example 2 The other steps are the same as Example 1.
[0127] Examples 3 to 5 As shown in Table 2 below, the polymers in Examples 3 to 5 were polymers 24, 26 and 27 obtained in Production Examples 24, 26 and 27, respectively, and the other steps were the same as in Example 1.
[0128] Examples 6 to 8 As shown in Table 2 below, the silane coupling agents in Examples 6 to 8 were 3-aminopropyltriethoxysilane, 3-(2,3-epoxypropoxy)propyltrimethoxysilane, and 3-(methacryloyloxy)propyltrimethoxysilane, respectively, and the other steps were the same as those in Example 1.
[0129] Examples 9 to 13 As shown in Table 2 below, the mass ratios of silicon dioxide particles to the silane coupling agent vinyltriethoxysilane in Examples 9 to 13 were 99.9:0.1, 99.4:0.6, 98.2:1.8, 98.0:2.0, and 97.6:2.4, respectively, and the average particle sizes Dv50 of the silicon dioxide particles modified with the silane coupling agent were 780 nm, 550 nm, 330 nm, 590 nm, and 980 nm, respectively, and the other steps were the same as those in Example 2.
[0130] Examples 14 to 17 As shown in Table 2 below, the mass ratios of the polymer to the silicon dioxide modified with the silane coupling agent in Examples 14 to 17 were 40:60, 50:50, 80:20, and 90:10, respectively, and the other steps were the same as those in Example 3.
[0131] Comparative Example 1 As shown in Table 2, the difference between Comparative Example 1 and Example 2 is that the adhesive composition does not contain a silane coupling agent, and the other steps are the same as those of Example 2.
[0132] Comparative Examples 2 to 3 As shown in Table 2, Comparative Examples 2-3 are distinguished from Example 1 in that the polymers used are polymers C1 and C2 obtained in Comparative Production Examples 1 and 2, respectively; the other steps are the same as in Example 1.
[0133] 2. Testing method: (1) Adhesion test between separator and positive electrode plate The battery positive plate was overlapped with the separator and placed in a hot press, and the hot press parameters were set to 25°C temperature, 10t pressure, and 30s time to produce a bonded separator / positive plate sample, which was then cut into a 150 x 20mm rectangular sample strip. One side of the positive plate of the rectangular sample strip was attached to a steel plate with double-sided tape, and the separator and positive plate were separated by a length of 2cm along the length at one end of the rectangular sample strip to produce a test specimen.
[0134] The steel plate was held horizontally and fixed with the lower fixture of a universal testing machine (Model CTM2100, Xie Qiang Testing Machinery Manufacturing (Shanghai) Co., Ltd.), and the peeled end of the separator described above was fixed with the upper fixture of the universal testing machine and connected to a tensile machine. The test conditions were set at a tensile speed of 20 mm / min, and the plate was pulled horizontally for 10 cm. After the tensile force stabilized, the value of the tensile force was recorded, and the adhesive strength between the separator and the electrode plate was obtained from the ratio of the tensile force value to the sample width. The test results are shown in Table 2.
[0135] (2) Battery cycle performance / capacity retention test Taking Example 1 as an example, the battery capacity retention test process is as follows: At 25°C, the battery prepared in Example 1 is charged to 4.3V at a constant current of 1 / 3C, then charged to a current of 0.05C at a constant voltage of 4.3V, left for 5 minutes, and discharged to 2.8V at 1 / 3C. The obtained discharge capacity is the initial capacity C0. The above steps are repeated for the same battery, and the discharge capacity C of the battery after the nth cycle is calculated. n Record the battery capacity retention rate P after each cycle. n is =(C n / C0) × 100%. In other words, the battery capacity retention rate at a specific number of cycles can be used to reflect the difference in cycle performance.
[0136] In Table 2, the battery capacity retention data corresponding to Example 1 is the data tested after 100 cycles under the above test conditions. The test process of the comparative example and other examples is the same as above. The test results are shown in Table 2.
[0137] [Table 2] TIFF0007635428000013.tif243168
[0138] As can be seen from the comparison between Examples 1-17 and Comparative Examples 1-3 in Table 2 above, the adhesive composition of the present application has good adhesive properties and is advantageous in improving the battery capacity retention rate of secondary batteries.
[0139] It should be noted that the present application is not limited to the above-mentioned embodiment. The above-mentioned embodiment is merely an example, and any embodiment having substantially the same configuration as the technical idea and achieving the same effect within the scope of the technical solution of the present application is included in the technical scope of the present application. In addition, various modifications that a person skilled in the art can make to the embodiment and other methods configured by combining some of the components in the embodiment are also included in the scope of the present application, within the scope of the purpose of the present application. [Explanation of symbols]
[0140] 1 Battery pack 2 Upper case 3 Lower housing 4 Battery Module 5 Secondary battery 51 cases 52 Electrode Assembly 53 Cover plate
Claims
1. An adhesive comprising a polymer and ceramic particles modified with a silane coupling agent, the polymer comprising structural units derived from a first class of monomers, a second class of monomers and a third class of monomers, the molar ratio of the first class of monomers to the second class of monomers and the third class of monomers being 50-58:40-44:2-6; The first class of monomers is selected from one or more compounds of formula I: 【Chemistry 1】 Here, R 1 is selected from a hydrogen atom and a linear or branched C1-6 alkyl group, and R 2 is selected from substituted or unsubstituted linear or branched C1-15 alkyl groups, C3-6 cycloalkyl groups and isobornyl groups, in which case the substituents are selected from hydroxyl groups and C1-6 linear alkyl groups; The second class of monomers is selected from one or more compounds of formula II: 【Chemistry 2】 Here, R 3 is selected from a hydrogen atom and a linear or branched C1-6 alkyl group; The third class of monomers is selected from one or more compounds of formula III: 【Chemistry 3】 Here, R 4 is selected from a hydrogen atom and a linear or branched C1-6 alkyl group, and R 5 is selected from a hydrogen atom, a hydroxy C1-6 alkyl group, and a C1-6 alkoxy group.
2. R 1 is selected from a hydrogen atom and a methyl group, and R 2 is selected from substituted or unsubstituted linear or branched C alkyl groups, in which case the substituent is a hydroxyl group, and / or R 3 is selected from a hydrogen atom and a methyl group, and / or R 4 is selected from a hydrogen atom and a methyl group, and R 5 is selected from a hydrogen atom, a hydroxy C1-4 alkyl group, and a C1-4 alkoxy group.
3. the first class of monomers being one or more selected from methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, n-propyl acrylate, cyclohexyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, lauryl methacrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, and / or the second type of monomer is acrylonitrile or methacrylonitrile, and / or The adhesive according to claim 1 or 2, wherein the third type of monomer is one or more selected from acrylamide, N-methylolacrylamide, and N-butoxymethacrylamide.
4. 3. The adhesive according to claim 1, wherein the molar ratio of the first type of monomer to the second type of monomer to the third type of monomer is 50-57:41-44:2-6.
5. The adhesive of claim 1 or 2, wherein the weight average molecular weight of the polymer is from 60,000 to 120,000, optionally from 63,300 to 118,800.
6. The adhesive of claim 1 or 2, wherein the average particle size Dv50 of the ceramic particles modified with the silane coupling agent is from 200 nm to 980 nm, more preferably from 200 nm to 600 nm, and even more preferably from 330 nm to 550 nm.
7. The silane coupling agent is one or more selected from the compounds of formula IV, 【Chemistry 4】 Here, R 6 , R 7 and R 8 are each independently selected from linear or branched C alkyl groups; R 9 is selected from a C2-6 alkenyl group and a C1-6 linear alkyl group, and at least one hydrogen atom on a terminal carbon atom of the C1-6 linear alkyl group is substituted with a substituent selected from an amino group, a 2,3-epoxypropoxy group, and a methacryloyloxy group; Optionally, R 6 , R 7 and R 8 are each independently selected from a methyl group and an ethyl group, and / or R 9 is selected from a vinyl group, a 3-aminopropyl group, a 3-(2,3-epoxypropoxy)propyl group, and a 3-(methacryloyloxy)propyl group; Optionally, the silane coupling agent is one or more selected from vinyltriethoxysilane, 3-aminopropyltriethoxysilane, 3-(2,3-epoxypropoxy)propyltrimethoxysilane and 3-(methacryloyloxy)propyltrimethoxysilane. The adhesive of claim 1 or 2.
8. The adhesive according to claim 1 or 2, wherein the weight ratio of the ceramic particles to the silane coupling agent is 97.5-99.9:0.1-2.5, more preferably 98.0-99.9:0.1-2.0, and even more preferably 98.2-99.4:0.6-1.
8.
9. The adhesive of claim 1 or 2, wherein the weight ratio of said polymer to said ceramic particles is 40-90:10-60, optionally 50-80:20-50.
10. The adhesive of claim 1 or 2, wherein the polymer coats the ceramic particles.
11. A separator comprising a base layer and a coating layer disposed on at least one surface of the base layer, the coating layer comprising the adhesive composition according to claim 1 or 2.
12. A secondary battery comprising the adhesive of claim 1.
13. A battery module comprising the secondary battery according to claim 12.
14. A battery pack comprising the battery module according to claim 13.
15. A power consuming device comprising at least one selected from the group consisting of the secondary battery according to claim 12, the battery module according to claim 13, and the battery pack according to claim 14.
Citation Information
Patent Citations
Battery separator, preparation method thereof and battery
CN109841779A
Diaphragm slurry, preparation method and application thereof
CN112259913A
Composite diaphragm, preparation method thereof and secondary battery
CN113851787A
Binder for secondary battery porous films, slurry composition for secondary battery porous films, porous film for secondary batteries, and secondary battery
JP2015185530A
Acrylonitrile copolymer binders and their applications in lithium-ion batteries
JP2019526693A